Asian Research in Mathematics Education Mapping the Field - Atweh, Bill.; Fan, Lianghuo; Vistro-Yu, Catherine P. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on the development of research in mathematics education cultures and its products from the perspective of local educators. It consists of contributions from Mainland China, Indonesia, Korea, Macao, Singapore, the Philippines, and Turkey. This book examines the development of the culture of research in the respective countries and also reviews the research conducted in the recent past in mathematics education. It takes a critical stance through identifying the various accomplishments, and identifying challenges for the future of research in terms of its diversification and quality. Divided into two sections, the first section considers factors around the development of a research culture in the respective countries by focusing on the means used to develop research expertise and quality. The second section consists of overviews of the area of research and methodologies conducted in mathematics education in the various countries, with the intention of highlighting the research topics conducted as well as discussing omissions of such research.
Section 1: Developing Research Culture in Mathematics Education -- Chapter 1. Building a Research Culture in Philippine Graduate Education: Reflections on Experiences in Mathematics Education -- Chapter 2. Development of Chinese Mmathematics Education Research Culture: A Case Study -- Chapter 3. The Evolution of Mathematics Education Research in Singapore -- Section 2: Overview of Mathematics Education Research -- Chapter 4. Critical Analysis of Mathematics Education Doctoral Dissertations in the Philippines: 2009 - 2021 -- Chapter 5. A Critical Review of Mathematics Education Research in Korea: Trends, Challenges, and Future Directions -- Chapter 6. Mathematics Education Research Trends in Turkey: International Research Context -- Chapter 7. Research and Research Culture in Mathematics Education: The Case in Macao, China -- Chapter 8. Trend in Mathematics Education Research in Indonesia. . .
Keywords: Mathematics; Education -- Research; Education and state; Mathematics Education; Educational Research; Educational Policy and Politics